Numerical evaluation and experimental validation of fluid flow behavior within an organ-on-a-chip model - Carvalho, Violeta Meneses (2024)
By combining biomaterials, cell culture, and microfluidic technology, organ-on-a-chip (OoC) platforms have the ability to reproduce the physiological microenvironment of human organs. For this reason, these advanced microfluidic devices have been used to resemble various diseases and investigate novel treatments. In addition to the experimental assessment, numerical studies of biodevices have been performed aiming at their improvement and optimization. Despite considerable progress in numerical modeling of biodevices, the validation of these computational models through comparison with experimental assays remains a significant gap in the current literature. This step is critical to ensure the accuracy and reliability of numerical models, and consequently enhance confidence in their predictive results. The aim of the present work is to develop a numerical model capable of reproducing the fluid flow behavior within an OoC, for future investigations, encompassing the geometry optimization.